Challenges of legal security in the constitutional system: The problematic of the balance between legislative change and the stability of the legal system - Benzaghou, Naziha; Benmammar, Sofiane (The International tax journal, 2025)
Legal security is one of the essential determinants of the validity of any constitution and its ability to ensure the conditions of the rule of law and the protection of fundamental rights and freedoms. This security consists in the legal system’s ability to provide behavioral predictability for citizens and economic and political actors, and to guarantee a reasonable stability of the legal rules that regulate public and private relations. However, the contemporary challenges represented by the pace of technological change, security risks, the economic crisis, and social unrest have generated increasing pressures on constitutional systems for rapid legal amendment or new legislation often at the expense of the stability of the legal order. This article examines the constitutional structure of the concept of legal security in the context of contemporary transformations, and analyzes the core issue represented by the balance between the state’s need for rapid legislative renewal in response to political, economic, and social developments, and the constitutional system’s concern to ensure the stability of the legal order and the predictability of legal rules to protect fundamental rights and freedoms.